The Dynamics of Technical-Tactical Actions Performed in Official Matches by the Teams “Sogdiana” and “Olmaliq” - Khayrulla Artikov; Adnan Mohsin Abbood (CV Media Inti Teknologi, 2025)
This article analyzes the dynamics of technical-tactical actions (TTA) performed during official matches by teams composed of skilled football players. Ongoing pedagogical observations were conducted on the players of teams participating in the Uzbekistan National Football Championship's top league during the 2023-2024 seasons. The research involved 42 football players from two teams competing in the country’s top league during the 2023 and 2024 championships. The average indicators of technical-tactical actions performed by the “Sogdiana” and “Olmaliq” teams during the matches at the beginning, middle, and end of the championship were identified and analyzed. The recorded indicators suggest that both the volume of TTAs and the movement across the field among players participating in the Uzbekistan National Championship are significantly lower compared to those of foreign players, highlighting a primarily “weak” development of their general and specific work capacity. However, in the official matches held in the middle and at the end of the championship, players of the “Olmaliq” team who regularly performed experimental relaxation exercises throughout the year showed progressive increases in the volume and efficiency of TTAs as well as in their physical and functional capacity levels.